Have questions about your preparation or an upcoming test? Need help modifying the Study Plan to meet your unique needs? No problem. Just book a Skype meeting with Brent to discuss these and any other questions you may have.

- Video Course
- Video Course Overview - READ FIRST
- General GMAT Strategies - 7 videos (all free)
- Data Sufficiency - 16 videos (all free)
- Arithmetic - 38 videos (some free)
- Powers and Roots - 36 videos (some free)
- Algebra and Equation Solving - 73 videos (some free)
- Word Problems - 48 videos (some free)
- Geometry - 42 videos (some free)
- Integer Properties - 38 videos (some free)
- Statistics - 20 videos (some free)
- Counting - 27 videos (some free)
- Probability - 23 videos (some free)
- Analytical Writing Assessment - 5 videos (all free)
- Reading Comprehension - 10 videos (all free)
- Critical Reasoning - 38 videos (some free)
- Sentence Correction - 70 videos (some free)
- Integrated Reasoning - 17 videos (some free)

- Study Guide
- Your Instructor
- Office Hours
- Extras
- Prices

## Comment on

Factoring - Quadratics## This is one of the questions

Which of the following equations has

a root in common with x^2 - 6x + 5 =

0?

(A) x^2 + 1 = 0

(B) x^2 - x - 2 =0

(C) x^2 - 10x - 5 =0

(D) 2x^2 - 2 =0

(E) x^2 - 2x - 3 =0

I understood the solution but I have a question:

How X^2+1=0? Is this even possible? X^2 could be either zero or a positive number.

## Question link: http://www

Question link: http://www.beatthegmat.com/common-root-t117001.html

Great question, Mohammad!

Not all equations have a solution. This equation (x^2 + 1 = 0) is one of them.

ASIDE: some students with an understanding of complex (aka imaginary) numbers, will say that there IS a solution. It's x = i (where i = √-1). However, the GMAT only covers REAL numbers, so we say that the equation x^2 + 1 = 0 has no REAL solution.

## Thanks. And great point on

## Hi Brent,

Great video! Just a quick question - how does one go about factoring a quadratic equations such as these ones:

1) 2x^2 + 9x + 9 = 0

This one factors out to be (2x + 3) (x + 3)

2) 2x^2 + x - 3

Factors out to (x - 1) (2x + 3)

I'm confused on how to separate factors such as 2x in individual expressions in the above examples.

Hope this question made sense!

## Hi BalysLTU,

Hi BalysLTU,

There's a formal technique for factoring quadratics where the coefficient of the x² is NOT 1, but for the purposes of the GMAT, we can typically apply the informal method describe below.

Here's a video of the formal technique: https://www.khanacademy.org/math/algebra/polynomial-factorization/factor...

On the GMAT, you'll typically see quadratic equations that look like the following:

x² - 2x - 15 = 0

x² + 8x + 12 = 0

x² - 7x + 10 = 0

However, if you do encounter a quadratic equation where the coefficient of the x² is NOT 1, then you can typically factor the expression by applying some number sense and testing some values.

Here's what I mean:

Given: 2x² + 9x + 9 = 0

Let's say the expression (2x² + 9x + 9) can be factored to look something like: (a + b)(c + d)

What can we conclude about some of the values?

Well, we know that ac = 2x² (applying the FOIL method)

If we limit ourselves to integer vales, then there's only one way to get a product of 2x²

That is, (2x)(x) = 2x²

So, we already know that 2x² + 9x + 9 = (2x + b)(x + d)

We also know that bd = 9

There aren't that many options where the product of two integers equals 9

One option is (1)(9) = 9

Another option is (3)(3) = 9

At this point, we can start TESTING some options...

How about b = 1 and d = 9

Plug in to get: (2x + 1)(x + 9)

Expand and simplify to get: (2x + 1)(x + 9) = 2x² + 19x + 9

The middle term (19x) is not right. We want 9x

TRY AGAIN

How about b = 3 and d = 3

Plug in to get: (2x + 3)(x + 3)

Expand and simplify to get: (2x + 3)(x + 3) = 2x² + 9x + 9

Perfect!

Done!

I'll leave it to you to try factoring the second expression.

Cheers,

Brent

## Hey!

How do you factorize x² - 10x - 5? I cant seem to think of two numbers that will add to be - 10 and multiply to be 5. Is it because it consists of two negatives? (Since its not x² + nx + p). I'm confused what to do when both the x term and the constant are negative, as opposed to two positives or one positive and one negative. Cheers!

## Good question, Byefox.

Good question, Byefox.

x² - 10x - 5 cannot be factored into the form (x + ?)(x - ?)

Can you tell me the details of the question that require the factorization of x² - 10x - 5? Perhaps there's an alternate approach.

Cheers,

Brent

## Hi Brent, for the following

If xy > 0, does (x - 1)(y - 1) = 1?

(1) x + y = xy

(2) x = y

statement is: x+y=xy

1) - clearly sufficient

2) - x^2=2x >>>> x=2

But the correct answer given is A. Can't figure why!

https://gmatclub.com/forum/if-xy-0-does-x-1-y-167337.html

## Hi Jalaj,

Hi Jalaj,

Here's my step-by-step solution: https://gmatclub.com/forum/if-xy-0-does-x-1-y-167337.html#p2112935

Cheers,

Brent

## Hi Brent, could you provide a

Which of the following equations has a root in common with x² − 6x + 5 = 0?

A. x² + 1 = 0

B. x² − x − 2 = 0

C. 2x² − 2 = 0

D. x² − 2x − 3 = 0

E. x² − 10x − 5 = 0

## Hi Jalaj,

Hi Jalaj,

I have a solution here: https://gmatclub.com/forum/which-of-the-following-equations-has-a-root-i...

Please let me know if you'd like me to clarify any steps.

Cheers,

Brent

## Hi Brent:

In the following question: https://www.beatthegmat.com/what-is-the-value-of-r-2-2rs-s-2-t297050.html

What is the value of r^2-2rs+s^2?

(1) s=4

(2) r-s=12

Why is statement 1 not sufficient?

We know that r^-2rs+s^2 is the same as (r-s)(r-s).

If we are given s=4.

Then our quadratic equation becomes (r-4)(r-s)=0. This gives us a definitive answer of r=4.

Could you kindly explain what I am overlooking?

## Question link: https://www

Question link: https://www.beatthegmat.com/what-is-the-value-of-r-2-2rs-s-2-t297050.html

For some reason, you have turned the EXPRESSION (r-s)(r-s) into an EQUATION (r-s)(r-s) = 0

There is no equation here.

We're asked to determine the value of (r-s)(r-s), but you are trying to find the value of r.

So, if s = 4, then (r - s)(r - s) = (r - 4)(r - 4)

Since we don't know the value of r, we can't find the value of (r - 4)(r - 4)

Does that help?

Cheers,

Brent

## Thanks Brent, you pointed out

## That's a very common error :-

That's a very common error :-)

## Hi Brent,

https://gmatclub.com/forum/if-ax-b-0-is-x-0-1-a-b-0-2-a-b-99749.html

Need your approach to answer this one. I used a very lengthy approach and still got the answer wrong.

ax + b = 0 > Case a. ax = -2 and b = 2 or Case b. ax = 2 and b = -2.

Case a can have 4 scenarios:ax = -2 and b = 2

1. a = 2 and x = -1

2. a = -2 and x = 1

3. a = -1 and x = 2

4. a = 1 and x = -2

Snt 1: a+b>0; only 1 and 4 fits and hence sufficient.

Used the same method for Snt 2. Could you help me identify where did I go wrong?

## Be careful; case 3 (a = -1

Be careful; case 3 (a = -1 and x = 2) also meets the condition that a+b > 0

Cheers,

Brent

## Oh no, yet again! Thanks for

## Speaking of silly mistakes .

Speaking of silly mistakes . . . . :-)

## Hi Brent,

I wanted to more clarity on the or condition shared here by Bunuel - https://gmatclub.com/forum/what-is-the-value-of-x-y-163356.html#p1937355

Please share more examples to understand the concept. I marked D considering B is also sufficient.

Warm Regards,

Pritish

## Bunuel's solution: https:/

Bunuel's solution: https://gmatclub.com/forum/what-is-the-value-of-x-y-163356.html#p1937355

This question highlights an important concept: If AB = 0, then EITHER A = 0 OR B = 0

For example, if AB = 0, then it COULD be the case that A = 0 and B = 1

Or it COULD be the case that A = 3 and B = 0

Or it COULD be the case that A = 0 and B = 0

Many students will incorrectly conclude that, if AB = 0, then A and B must BOTH equal zero. As you can see by the above examples, this is not necessarily true.

Consider this quadratic equation: x² + 2x - 15 = 0

Factor to get: (x + 5)(x - 3) = 0

This means that EITHER x + 5 = 0 OR x - 3 = 0

So, EITHER x = -5 OR x = 3

So, if a DS question asked "What is the value of x?" and statement 1 was x² + 2x - 15 = 0, then statement 1 is NOT sufficient (since x can be either -5 or 3)

Most of the linked questions DS in the Reinforcement Activities box at https://www.gmatprepnow.com/module/gmat-algebra-and-equation-solving/vid... will feature a similar feature.

For example:

- https://gmatclub.com/forum/if-y-x-2-6x-9-what-is-the-value-of-x-221249.html

- https://gmatclub.com/forum/what-is-the-value-of-integer-n-243142.html

- https://gmatclub.com/forum/is-y-214659.html

Cheers,

Brent

## https://gmatclub.com/forum

Hi Brent! Just a small error. Here we can eliminate option A since it's actually √91 .. I think you put √81 by mistake.

Amazing videos btw. Thank you!

## Thanks for the heads up!

Thanks for the heads up!

I edited my response accordingly.

Cheers,

Brent

## https://gmatclub.com/forum

Hi Brent. Couldn't quite understand Bunuel's solution for statement 2. I put D, but apparently statement 2 is not sufficient. Please could you clarify?

Thanks before hand. :)

## Question link: https:/

Question link: https://gmatclub.com/forum/what-is-the-value-of-x-y-163356.html

TARGET QUESTION: What is the value of x - y?

Statement 2: x² - y² = 0

Factor: (x + y)(x - y) = 0

So, EITHER x + y = 0, OR x - y = 0

So, x - y may or may not equal 0

Not sufficient.

Alternatively, we could test some cases.

case a) x = 1 and y = -1 (this satisfies the condition that x² - y² = 0)

In this case, the answer to the target question is x - y = 2

case b) x = 1 and y = 1

In this case, the answer to the target question is x - y = 0

Not sufficient.

Cheers,

Brent

## So, this EITHER OR rule works

Cheers :)

## That's correct.

That's correct.

If x² + 6x + 5 = 0, then we can conclude that either x = -5 or x = -1 (but not both)

Cheers,

Brent

## Add a comment